PENGEMBANGAN MATERI TEMATIK RAGAM SENI KARYA DENGAN GAMES PUZZLE UNTUK MENGASAH OTAK ANAK PADA SISWA KELAS RENDAH MI NW LINGKOK TELU - Hamzani Aulia Rahman; Aninditya Sri Nugraheni (STKIP Persada Khatulistiwa Sintang, 2021)
This research aims to give learners a stimulus about the variety of art in thematic which is one of the sustainable material models with various descriptions in local traditions and wisdom in the community by explaining the various understandings and history in it with facts and concepts later in order to hone their brains about culture. Research method in this ha used is Waterfall Research and Development model with stages ranging from analysis, design, implemntasi and testing and the end of maintenance. Then the results of the study showed from the material content test or produck got an average of 75.6% with a decent category then researchers tried the test and implementation to students numbering 10 people and got an average of 81.6% categorized into satisfaction with a score of 80 in the category agreed. Therefore, it can be concluded that puzzle media for learning facilities in sharpening the brain of learners can improve their abilities and make learning fun.